2011
DOI: 10.1073/pnas.1100489108
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent chimeric RNAs enriched in human prostate cancer identified by deep sequencing

Abstract: Transcription-induced chimeric RNAs, possessing sequences from different genes, are expected to increase the proteomic diversity through chimeric proteins or altered regulation. Despite their importance, few studies have focused on chimeric RNAs especially regarding their presence/roles in human cancers. By deep sequencing the transcriptome of 20 human prostate cancer and 10 matched benign prostate tissues, we obtained 1.3 billion sequence reads, which led to the identification of 2,369 chimeric RNA candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 20 publications
(35 reference statements)
6
166
2
1
Order By: Relevance
“…Recent studies incorporating systematic in silico analysis and pairedend RNA sequencing have identifi ed many chimeric RNAs involving 2 adjacent genes (14,15). No functional role of these chimeras has yet been identifi ed and the underlying mechanism remains elusive (13,15). The terms "gene readthrough" and "co-transcription and intergenic splicing" have been used to describe these chimeric RNAs that join neighboring gene fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies incorporating systematic in silico analysis and pairedend RNA sequencing have identifi ed many chimeric RNAs involving 2 adjacent genes (14,15). No functional role of these chimeras has yet been identifi ed and the underlying mechanism remains elusive (13,15). The terms "gene readthrough" and "co-transcription and intergenic splicing" have been used to describe these chimeric RNAs that join neighboring gene fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Judging by sequence alone, it is impossible to discern these 2 types of events. In fact, RNA trans-splicing may also have a higher incidence rate among genes that are close to each other (15).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-seq data GSE22260 (16) were downloaded from the Gene Expression Omnibus (www.ncbi.nlm.nih.gov) database, including 4 prostate cancer samples (GSM554078, GSM554082, GSM554086 and GSM554088) and 4 matched normal tissues samples (GSM554118, GSM554120, GSM554122 and GSM554124), respectively. The Gleason score of the four cancer samples were 7, 7, 7 and 6 (18).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of RNA-seq data, the transcriptome profiles of primary prostate cancer are identified, including gene fusions, long non-coding RNAs, alternative splicing and somatic In the present study, raw RNA-seq data from the study by Kannan et al (16) was downloaded from the National Center for Biotechnology Information database and analyzed by a number of bioinformatics methods. First, DEGs between prostate cancer samples and normal control samples were identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that a fraction of fusion genes are transcribed and produce chimeric RNA molecules that are made of RNAs from two or more genes. In fact, many so-called "fusion genes" in cancer cells (15) are initially discovered not based on the fusion genes themselves at the genome DNA level but rather on identification of their fusion RNA products using the RT-PCR approach that detects fusion cDNAs in various cases, without necessarily confirming the existence of a corresponding gene in the cell genome (16,17). With the expansion of expressed sequence tag (EST) and cDNA databases and improvement of next generation sequencing technologies, an increased number of fusion RNAs and fusion genes have been identified and validated in recent years (2-4), especially in cancers.…”
Section: Chimeric Rnas Produced From Fusion Genesmentioning
confidence: 99%